A Socially Assistive Robot for Long-Term Cardiac Rehabilitation in the Real World - Céspedes, Nathalia; Irfan, Bahar; Senft, Emmanuel; Cifuentes, Carlos A.; Gutierrez, Luisa F.; Rincon-Roncancio, Mónica; Belpaeme, Tony; Múnera, Marcela (Frontiers in Neurorobotics, 2021)
Can a socially assistive robot support patients in cardiovascular rehabilitation? To answer this question, in collaboration with medical specialists, we designed and conducted a real-world long-term study, lasting 2.5 years, at the Fundacion Cardioinfantil-Instituto de Cardiologıa clinic (Bogota, Colombia) within the context of the outpatient phase of their cardiac rehabilitation programme. The study aimed to compare the patient progress and adherence in the conventional cardiac rehabilitation programme (control condition) with the deployment of a fully autonomous socially assistive robot that continuously monitored the patients during exercise to provide immediate feedback and motivation based on sensory measures (robot condition). The explicit aim of the social robot is to improve patient motivation and increase adherence to the programme. We recruited 15 patients per condition. The cardiac rehabilitation programme was designed to last 36 sessions (18 weeks) per patient. The findings show that adherence increases by 15% and the optimal recovery heart rate after one minute of the training end (> 22 bpm, successful Cardiac Rehabilitation programme performance) was reached successfully in the robot condition. In contrast, the patients who were not assisted by the robot did not achieve the optimal recovery heart rate in all stages. Moreover, we also show that the healthcare staff and patients’ attitudes towards the robot are mainly positive. The benefits are acknowledged by those who worked in collaboration with the robot.